Projective Synchronization of Bidirectionally Coupled Chaotic Systems via Linear Transformations - Khan, Mohammad Ali; Poria, Swarup (International Journal of Applied Mathematical Research, 2012)
Several important properties of chaos synchronization of bidirectionally coupled systems remain still unexplored. This paper designes a new projective synchronization scheme for generalized bidirectionally coupled chaotic systems via linear transformations.The proposed synchronization scheme of bidirectionally coupled chaotic systems are discussed taking coupled unified chaotic systems. Simulation results are presented to show the effectiveness of the proposed scheme.